Ecotourism Management Structuring at The Salak Mountain II Resort, Halimun Salak National Park - Kusumoarto, Andrianto; Hidayat, Ryan; Jubei, Siti; Ernawati, Atie (E-Journal of Tourism; Volume 6 Number 2 (September 2019), 2019)
The Salak Mountain II Resort Area, Halimun Salak National Park has several ecotourism objects that have a good ecotourist attraction. In the Salak Mountain II Resort area,  there are several actors who have a role in management, where there are several obstacles faced during the course of the activity. The objectives in this study are 1) identifying elements in the management structure variables; 2) analyze the goals variable of ecotourism development, needs variable of ecotourism development, activity programs variable of ecotourism development, obstacles variable of ecotourism development, and actors variable of ecotourism development; 3) making the model of ecotourism management structuring. The method used in this study is descriptive qualitative with Interpretive Structural Modeling (ISM) analysis. The results of the study shown that the desired goals in managing the area are the conservation of natural resources and their ecosystems, and providing education to the community about environmental management. The desired need in area management is the existence of ecotourism legality. Some of the desired program activities in regional development and management are agrotourism, local cultural and artistic attractions, ecotourism, and natural recreation. Some obstacles in the development and management of the area are the limited human resources that have knowledge, skills in managing ecotourism areas and changes in the status of the utilization zone to the ecotourism zone. Salak Mountain II Resort Office, Koperasi Khalifah, Village-Owned Business Entity are actors who have very strong driving factors and function as variable linkage. Each element in the variable has different strengths as a driver and dependency.